Biomass Production and Nutrient Content Animal Feed in Kuantan Singingi District - Infitria Infitria; Pajri Anwar; Jiyanto Jiyanto (UNIVERSITAS ISLAM LAMONGAN, 2021)
Forage is a major requirement in increasing ruminant livestock production. Kuantan Singingi Regency is a district that has quite a lot of grasslands whose production and quality of forage are unknown, so this study aims to determine the production and nutritional content of forages in Kuantan Singingi Regency. This research consisted of three stages, survey (field observation and location determination), forage sampling, and nutrient quality analysis. Forage samples were taken in 4 sub-districts, namely the Districts of Central Kuantan, Sentajo Raya, Gunung Toar and Kuantan Mudik. 5 locations were taken for each sub-district, 4 points for each location were taken. The tools used for forage sampling consisted of a 0.5 x 0.5 m2 quadrant, grass shears, sickle, plastic bags of size 10 and size 2 kg, sacks, plastic ropes, and stationery. The analysis of nutrient quality using forage samples in 4 districts using proximate analysis. Forage production data and forage nutrient content were statistically analyzed using analysis of variance (ANOVA). The results showed that there were differences in production and nutrient content in each sub-district P<0.05. Fresh biomass production showed a significant effect of P<0.05. Fresh forage production ranged from 111.67±16.45 Kg FW/ha/day, while dry forage production ranged from 23.80±5.29 Kg to 187.04±67.35 Kg. The conclusion of this study is that the production and nutritional content of forage in Kuantan Singingi Regency is relatively low, the production of DW/ha/day is 23.80-40.35 Kg, and the CP ranges from 7.85-10.55% DW.